Limited-time scarcity and competitive arousal in E-commerce. Issue 5 (20th October 2022) - Broeder, Peter; Wentink, Eileen
ABSTRACT: In their web stores, retailers are increasingly using scarcity as a strategy to influence customers' perceptions and purchase behaviour. This study aims to investigate the effect of limited-time promotions on purchase intention while examining the mediating roles of perceived scarcity and competitive arousal as predictors as well as the moderating role of consumers' cultural background. An experimental survey is carried out with two conditions for a product offer in a web store: an offer with a limited-time availability notice; and an offer with a non-limited (in-stock) notice. In total, 208 Europeans (originating from Italy, an individualistic-masculine society, and the Netherlands, an individualistic-feminine society) participated in the study. The results demonstrate that a limited-time notice does not directly generate higher purchase intention compared to a non-limited-time notice. Interestingly, another major finding pertains to the indirect effects on purchase intention. Specifically, a limited-time availability notice creates higher perceived scarcity and subsequently activates higher perceived competition, which, in turn, leads to higher purchase intention. However, this indirect effect on purchase intention emerged only for the Italian consumers, and not for the Dutch consumers, participating in this study.